Occurrence and predictors of abortion among women of the reproductive age group in a block of Darjeeling District, West Bengal, India - Pallabi Dasgupta; Romy Biswas; Dilip Kumar Das; Jayanta Kumar Roy (Wolters Kluwer Medknow Publications, 2019)
Background: Despite being a sensitive and less explored issue, abortion is a major preventable cause of maternal morbidity and mortality affecting millions of women in developing countries. Objectives: The study aimed to determine the occurrence, nature, and predictors of abortion among women in the reproductive age group in Naxalbari block of Darjeeling district. Methods: A community-based cross-sectional study was conducted in Naxalbari block of Darjeeling district, West Bengal, India, from May 2015 to April 2016, among 420 women aged 15-49 years selected from 30 villages by cluster sampling technique. A predesigned, pretested interview schedule validated in the local vernacular was used. Binary logistic regression was used for finding out predictors of abortion among ever-pregnant women. Results: Lifetime occurrence of abortion was 33.6%. Among total 178 events of abortion, 51.7% were spontaneous and 48.3% induced. Majority of spontaneous abortions events were attended by a doctor (73.9%). About 59.3% of induced abortions were illegal, and unwanted pregnancy was major reason (62.4%) for induced abortion. Private facilities and over the counter drugs were preferred. Lower education, nuclear family, number of children <2, not having male child, domestic violence during pregnancy were significant predictors of abortion. Conclusions: Illegal abortions were highly prevalent in the area. Unwanted pregnancies hint toward unmet needs of family planning. Stigma and poor awareness were the root cause of not visiting a health facility in case of abortions. Building up of better infrastructure, better orientation of frontline workers, non-judgemental and confidential services will attract women to in government facilities.